PLAIN-LANGUAGE APPROACH IN LEGISLATIVE DRAFTING: A PERSPECTIVE FROM POLAND - ZYCH, Natalia (Comparative Legilinguistics, 2019)
The purpose of this research is to explore plain-language postulates reflecting on legal drafting assumptions since legal acts should be precise, clear and express with no doubts the intention of the legislator. The aim of this project is to commence discussion about improving the clarity of Polish consumer law based on selected plain-language techniques. This article agrees that the aspiration to make the law comprehensible for all subjects is an idealistic postulate. Ultimately, despite this, legislators’ obligation is to make an effort to increase the intelligibility of legislation wherever it is possible.